Seaweed communities of inter-tidal rocky shores around Bintulu, Malaysia - Wong, Siaw Chia (2013)
Assessments (environmental relationship, diversity and chemical composition) on seaweed communities were carried out at inter-tidal rocky shores around Bintulu, Sarawak from January to October 2008. A total of 35 species of seaweeds were recorded from five rocky shores: Tg. Batu (15 species), Telekom Beach (22 species), Similajau National Park (21 species), Kuala Similajau (27 species) and Kg. Kuala Nyalau (28 species). Rhodophyta was the most diverse division followed by Chlorophyta and Phaeophyta. There was no distinct zonation for seaweed distribution in all rocky shores with species of Chlorophyta, Phaeophyta and Rhodophyta divisions were recorded at different level of inter-tidal (lower, middle and higher) shores and overlapped. Diverse life forms of seaweed were observed as adaption to the environment with many microhabitats. Five types of seaweed life forms were identified namely epilithic, epipelic, epiphytic, epizoic and drift. The same seaweed species can be found in any of the mode of life form such as Ulva intestinalis, Padina minor and Amphiroa fragilissima. However, epilithic seaweeds (45-56.76%) occurred to be the most occurring life form at all study sites and followed by epizoic seaweeds (23.64- 33.33%). Based on Bray-Curtis 70% similarity evaluation, three distinct clusters on the species occurrence in relation to months were observed at Tg. Batu, six at Telekom Beach, two at Similajau National Park, two at Kuala Similajau and three at Kg. Kuala Nyalau. Jaccard community similarity coefficient index showed that seaweed from Kuala Similajau and Kg. Kuala Nyalau were most similar. Based on BVSTEP analysis, combination of four physical variables (salinity, turbidity, conductivity and total suspended solid) with Spearman rank correlation (ρ) 0.877 at Telekom Beach and a combination of two chemical variables (ammonium and orthophosphate) with (ρ) 0.771 at Kg. Kuala Nyalau were the best combinations for occurrence and distribution of seaweed at each site. No specific variable was recorded e.g. salinity at Similajau National Park with (ρ) 0.853 and nitrite at Tg. Batu with (ρ) 0.580. There were significant difference (p<0.01) of proximate composition and minerals between selected seaweed species. Moisture content was found highest in Rhodophyta (82.68-88.56%) and ash highest in Chlorophyta (23.79-32.50%). Crude protein, crude fat, crude fiber were highest in Padina minor (6.36% of dry matter of 100 g of plant), Acetabularia major (0.84%) and Anadyomene plicata (16.77%). Acanthophora spicifera contained highest percentage of total carbohydrate with 67.32%. This study showed seaweeds contained high quantity of macro-minerals (Ca, Mg, N and K) ranged from 143.73-3360.33 mg/100g and micro-minerals (Fe, Zn, Cu and Mn) ranged from 1.34-650.81 mg/100g.